(3h-4)(2h+3)=(3h-2)(2h+1)

Simple and best practice solution for (3h-4)(2h+3)=(3h-2)(2h+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3h-4)(2h+3)=(3h-2)(2h+1) equation:


Simplifying
(3h + -4)(2h + 3) = (3h + -2)(2h + 1)

Reorder the terms:
(-4 + 3h)(2h + 3) = (3h + -2)(2h + 1)

Reorder the terms:
(-4 + 3h)(3 + 2h) = (3h + -2)(2h + 1)

Multiply (-4 + 3h) * (3 + 2h)
(-4(3 + 2h) + 3h * (3 + 2h)) = (3h + -2)(2h + 1)
((3 * -4 + 2h * -4) + 3h * (3 + 2h)) = (3h + -2)(2h + 1)
((-12 + -8h) + 3h * (3 + 2h)) = (3h + -2)(2h + 1)
(-12 + -8h + (3 * 3h + 2h * 3h)) = (3h + -2)(2h + 1)
(-12 + -8h + (9h + 6h2)) = (3h + -2)(2h + 1)

Combine like terms: -8h + 9h = 1h
(-12 + 1h + 6h2) = (3h + -2)(2h + 1)

Reorder the terms:
-12 + 1h + 6h2 = (-2 + 3h)(2h + 1)

Reorder the terms:
-12 + 1h + 6h2 = (-2 + 3h)(1 + 2h)

Multiply (-2 + 3h) * (1 + 2h)
-12 + 1h + 6h2 = (-2(1 + 2h) + 3h * (1 + 2h))
-12 + 1h + 6h2 = ((1 * -2 + 2h * -2) + 3h * (1 + 2h))
-12 + 1h + 6h2 = ((-2 + -4h) + 3h * (1 + 2h))
-12 + 1h + 6h2 = (-2 + -4h + (1 * 3h + 2h * 3h))
-12 + 1h + 6h2 = (-2 + -4h + (3h + 6h2))

Combine like terms: -4h + 3h = -1h
-12 + 1h + 6h2 = (-2 + -1h + 6h2)

Add '-6h2' to each side of the equation.
-12 + 1h + 6h2 + -6h2 = -2 + -1h + 6h2 + -6h2

Combine like terms: 6h2 + -6h2 = 0
-12 + 1h + 0 = -2 + -1h + 6h2 + -6h2
-12 + 1h = -2 + -1h + 6h2 + -6h2

Combine like terms: 6h2 + -6h2 = 0
-12 + 1h = -2 + -1h + 0
-12 + 1h = -2 + -1h

Solving
-12 + 1h = -2 + -1h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add 'h' to each side of the equation.
-12 + 1h + h = -2 + -1h + h

Combine like terms: 1h + h = 2h
-12 + 2h = -2 + -1h + h

Combine like terms: -1h + h = 0
-12 + 2h = -2 + 0
-12 + 2h = -2

Add '12' to each side of the equation.
-12 + 12 + 2h = -2 + 12

Combine like terms: -12 + 12 = 0
0 + 2h = -2 + 12
2h = -2 + 12

Combine like terms: -2 + 12 = 10
2h = 10

Divide each side by '2'.
h = 5

Simplifying
h = 5

See similar equations:

| 5log(3x-2)=3 | | x^3+2x^3=5 | | 3x+4y+7z=12 | | 3-2lnx=6 | | (4+y)(3y-8)=0 | | 7/2-9(-1)/2 | | 12/3(x=3)=1 | | 3y=5x-(1) | | 4(x-4)-8x=4 | | 3x-4+-2x=-5+5x | | 9x=3+7x | | x:17=2 | | 16x+8y+40x= | | y=-0.60*45+141 | | y=-0.60*35+141 | | 8+5x=-20+x | | x^2-12x-1=-3 | | y=-0.60*25+141 | | 6=5(x+2)-7x | | ln(t)-2= | | 1xY-60xX= | | 13Y-12X+14Z=12Y+14Z+48X | | -5x+2y+z= | | 5x+2y-z= | | 15x^2+10x-9=0 | | 2(5)=16-(-6) | | -49=2x+3x+6 | | X+7=14X+7-7 | | 145-342=2 | | 6x+7-7x=3 | | -10x=-4+2x | | 8=2(2c-5)c |

Equations solver categories